Production and operations management : Strategies and tactics - Heizer, Jay.; Render, Barry (Boston : Allyn and Bacon, Inc., 1988)
This book is intended to provide you with a current, complete, and practical introduction to the field.
Part One. Introduction -- Part Two. Decision-making techniques in P/OM -- Part Three. Strategic decisions in P/OM -- Part Four. Tactical decisions in P/OM -- Part Five. Computer models for P/OM.
Includes bibliographical references and index.
Keywords: PRODUCTION MANAGEMENT